Professional values and attitude of psychiatric social workers toward involuntary hospitalization of psychiatric patients. (July 2013) - Wu, Hui-Ching; Tang, I-Chang; Lin, Wan-I; Chang, Li-Hsing
Summary: In Taiwan, a 2007 Mental Health Act amendment stipulated to better protect patient autonomy and human rights based on a psychiatric disease assessment and a review committee consisting of several specialists, including psychiatric social workers. In 2009, involuntary hospitalization rates had not decreased but had increased to more than 90 percent. Social workers are obligated to advocate the rights of the individual in their ward. This study investigated the attitude of 235 psychiatric social workers toward coercion and the human rights of psychiatric patients in the process. Findings: Most considered involuntary hospitalization as a means providing care and security, and supported its use. Most favored patient rights to a good environment and daily life over their right to refuse treatment and the right to make legal decisions. Gender, educational level, and working experience at psychiatric facilities were found to be associated with attitudes toward coercion and the rights of involuntarily hospitalized patients. Multivariate regression revealed a social worker's holding a view that coercive hospitalization as offensive or therapeutic could predict a higher regard for the human rights of psychiatric patients. Applications: Conflicts between the role of a psychiatric social worker as patient advocate and his or her participation in a committee dedicated to protecting the patient and society from harm can be source of distress for some social workers. Future studies might want to focus how to best prepare future social workers for this role or focus on legal changes that could be instigated to better ensure patient autonomy.